Ядерный топливный цикл - Григорьева, О. С. (НТУ "ХПИ", 2008)
Розглянуто стан атомної промисловості у світі. Показано переваги використання уран-торієвого паливного циклу й недоліки сучасного уран-плутонієвого, а також переваги атомної енергетики в цілому перед іншими видами виробництва енергії. Показано стан атомної промисловості України й напрямки її розвитку.

The state of atomic industry is considered in the world. Advantages of the use of uran-torievogo of fuel cycle and lacks of modern uran-plutonievogo, and also advantages of atomic energy, are rotined on the whole before other types of production of energy. The state of atomic industry of Ukraine and direction of its development is rotined.
Nuclear fuel cycle
Keywords: ядерные изотопы; уран-плутониевый цикл; энергетические реакторы; радиоактивные отходы